2021
DOI: 10.1152/ajpheart.00123.2021
|View full text |Cite
|
Sign up to set email alerts
|

Childhood psychosocial stress is linked with impaired vascular endothelial function, lower SIRT1, and oxidative stress in young adulthood

Abstract: Adverse childhood experiences (ACEs) are psychosocial stressors that occur during sensitive developmental windows and are associated with increased lifetime cardiovascular disease (CVD) risk in a dose-dependent manner. Vascular endothelial dysfunction is a pathophysiological mechanism that promotes hypertension and CVD, and may be a mechanism by which ACEs contribute to lifetime CVD risk. We examined whether exposure to ACEs is associated with reduced vascular endothelial function (VEF) in otherwise healthy, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
(61 reference statements)
2
18
0
Order By: Relevance
“… 46 Similar outcomes have been recently confirmed in young adults exposed to ACEs with comparable associations identified between macrovascular function and the reported number of ACEs. 9 Current results extend previous findings and identify that individuals who experienced adversity during childhood also present with a significantly diminished vascular endothelial function both in the macro- and the micro-vasculature. Endothelial cells, and therefore endothelial dysfunction, differ in structure and phenotype, depending on the vessel type, and macro and microvessels respond differently to insults.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 46 Similar outcomes have been recently confirmed in young adults exposed to ACEs with comparable associations identified between macrovascular function and the reported number of ACEs. 9 Current results extend previous findings and identify that individuals who experienced adversity during childhood also present with a significantly diminished vascular endothelial function both in the macro- and the micro-vasculature. Endothelial cells, and therefore endothelial dysfunction, differ in structure and phenotype, depending on the vessel type, and macro and microvessels respond differently to insults.…”
Section: Discussionsupporting
confidence: 88%
“… 3–5 Vascular endothelial dysfunction, a well-established precursor of CVD, 6 is an important mediator in the ACE-induced increase in CVD risk. 7 Prevailing data in the literature supports that young adults exposed to ACE exhibit greater peripheral vascular resistance, augmented arterial stiffness, and reduced endothelial function, 8 , 9 all independent predictors of CVD events.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence regarding the pathophysiological mechanisms by which ACEs promote CVD largely emerged from pre-clinical, mouse models of early life stress, such as maternal separation with early weaning 4 . Recently, Jenkins et al 5 translated the preclinical evidence on ACEs and vascular function to young adults. Specifically, young adult women (∼20 years old) with moderate-to-severe (≥4) ACE exposure exhibited endothelial dysfunction, as measured by the flow mediated-dilation (FMD) technique.…”
Section: A Perspective On “The Link Between Childhood Adversity and C...mentioning
confidence: 99%
“…Similarly, Jenkins et al also found that vascular dysfunction was present in those with ACEs without deviations in traditional risk factors. 5 While ACEs are associated with increased likelihood of risky health behaviors, it appears that the association between ACEs and CVD may be independent of certain risky behaviors. For example, Jenkins et al 5 excluded individuals who smoked or used illicit drugs, and the ACEs cohort was matched to the control group for physical activity status.…”
Section: A Perspective On “The Link Between Childhood Adversity and C...mentioning
confidence: 99%
See 1 more Smart Citation